Vaginal Electrical Impedance of Cervico-Vaginal Mucus in Relation to Fertility in Crossbred Cows and Heifers - Ningwal, D.; Nema, S.P.; Kumar, S.; Kushwah, A.; Shivhare, M.; Bhardwaz, A. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A study was carried out on crossbred cows (n=20) and heifers (n=20) belonging to the Dairy farm of College of Veterinary Science and Animal Husbandry, Mhow and clinical cases of progressive farmers brought for AI to the Teaching Veterinary Clinical Complex and at the doorstep of farmers in nearby villages. All the animals were examined for vaginal electrical impedance (reading of draminski) on day 0, 7th and 45th of AI. Pregnancy was confirmed by rectal palpation after 2 months of insemination. There was highly significant (P<0.01) difference in the electrical impedance of cervico-vaginal mucus (CVM) at day 0, 7th and 45th in conceived animals (87.27±1.12, 106.29±0.99 128.63±1.05 reading of draminski) with increasing trend, whilst in non-conceived animals, the value on day 7th was significantly (P<0.01) higher than at day 0 and 45th which did not differ significantly (102.30±1.32 vs. 85.12±0.81 and 87.43±1.20 reading of draminski).